Hubungan Antara Interaksi Teman Sebaya Dengan Orientasi Masa Depan Pada Mahasiswa Universitas Muhammadiyah Surakarta - Lathifah, Azizaini, Soleh Amin, M. Si, Psi (2017)
Future orientation is a description of individual who sees himself in the future, it includes aims, expectations, and how to achieve that goal. One of the factors that affect the future orientation is peers. This study aims to determine the relationship between peer interaction with future-iented, the level of future orientation and effective contribution from the interaction of peers to the rientation of the future. Researchers used quantitative methods to achieve the objectives of this research. The subjects were the final semester students in Muhammadiyah University of Surakarta totaling 120 students. The results showed a correlation coefficient (r) of 0.625 with significance (p) = 0.000 (p <0.01). This indicated a significant positive correlation between peer interaction with future-oriented to the final semester students. The future orientation of research subjects is high, peer interaction research subject is high. Effective contribution from peer interaction by 39.06% against future orientation.